The comparison of the use of bread waste and milled corn as a source of energy in concentrate to the weight and percentage of external non-carcass components of female local goats - Dandy, Dandy; Abdullah, Abdullah (FAPETKAN UNTAD, 2020)
This study aims to determine the comparison of the use of bread waste and milled corn as a source of energy in concentrate to the weight and percentage of external non-carcass components of female local goats. This research was conducted from January 1 - April 23, 2020 at CV. Prima Breed, Tondo Village, Mantikulore District, Palu City, Central Sulawesi. The number of livestock used in this study was 12 female local goats aged ± 10 months with a weight range of 10-12 kg. The study used a two-treatment comparison test with t-test statistical analysis. The treatments in this study were: P1 = Giving concentrate with the basic ingredient of an energy source is milled corn + Panicum sarmentosum Roxburg (Roxb) ad-libitum and P2 = Provision of concentrate with the basic ingredient of energy sources is bread waste + Panicum sarmentosum Roxburg (Roxb) ad-libitum . The results of the t-test statistical analysis showed that the provision of concentrate + bread waste + milled corn gave a significant difference to the percentage of the external non-carcass components of local goats, while the provision of concentrate + bread and the provision of concentrate + ground corn did not give a significant difference to the weight of the non-carcass components external local goats.